The documentary process in the play Mi Vida Después: the transformation of livingness into experience (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
The article proposes an analysis of the play Mi Vida Después, by the Argentine director Lola Arias, considering how the combination of testimonial elements, representation, and document display establishes temporal overlaps in the play. The time of the Argentine military dictatorship, lived by the actresses and actors when they were still children, is put into perspective with the current adult time, configuring the time of the representation itself. We analyze this interplay of temporalities from the contrast between the notions of "experience" and "lived experience" in Walter Benjamin's work and, especially, from Raymond Williams's concept of "structure of feelings." Taking into account this overlapping of temporalities, we finally consider whether a play from thirteen years ago, created in the cultural and social context of Argentina, would have anything to say to Brazil today.
Keywords: political theater; theater and audiovisual; documentary theater; Lola Arias; Raymond Williams